Preface: Arable Land Quality: Observation, Estimation, Optimization, and Application - Sijing Ye; Changqing Song; Yakov Kuzyakov; Feng Cheng; Xiangbin Kong; Zhe Feng; Peichao Gao (Land, 2022)
Food security is a worldwide challenge that is related to the basic human needs of sustainable development [...]